A Single Case Study on the Role of Some Ayurvedic Medicine in the Management of Pittaja Visarpa w.s.r to Herpes Zoster - Bakuli, Bodhisattwa; Mahapatra, P B Kar (International Research Journal of Ayurveda & Yoga, 2022)
The name Herpes Zoster is derived from Herpein, meaning to creep; zoster, meaning gridle. While varicella is typically a disease of childhood, herpes zoster is an infectious disease,. It is the reactivation of chicken pox virus. It is commonly an episode of unilateral maculopapular painful rash and it appears recurrently in human due to suppressed immunity of an individual and the recurrence rate can be high as 13.26 % and Zoster mortality is presently elevated in country Severity effects with HIV/AIDS pandemic. The features of Zoster are more or less similar to the features of Pittaja Visarpa of Ayurveda. The initial Modern /Allopathic management is not satisfactory. As Visarpa is a skin disease having the features like and there is an indisposition characterization with rapidly spreading inflammation of skin. The main signs and symptoms of Visarpa include with a throbbing or prickly or stabbing pain, lassitude, horripilation, appearance of deep pink – colored and waxy patches on the skin with itching. The therapeutic regiments of Modern medicine are mostly immunosuppressive as well as having lots of adverse effects so considering those views a safe and effective Ayurvedic modalities have been introduce here. In present study orally Laxmivilash Rasa 500 mg, Gandhak Rasayan 500 mg, Sudarshan Ghana Vati 500 mg, and Brihat Haridra Khanda 3 grm have been given twice daily along with local application of Marichadi Taila. After 15 days of therapy satisfactory curative effect have been observed